2017
DOI: 10.1371/journal.pone.0182130
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel unsupervised single-particle cryo-EM data clustering via statistical manifold learning

Abstract: Structural heterogeneity in single-particle cryo-electron microscopy (cryo-EM) data represents a major challenge for high-resolution structure determination. Unsupervised classification may serve as the first step in the assessment of structural heterogeneity. However, traditional algorithms for unsupervised classification, such as K-means clustering and maximum likelihood optimization, may classify images into wrong classes with decreasing signal-to-noise-ratio (SNR) in the image data, yet demand increased co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 50 publications
(113 reference statements)
0
65
0
Order By: Relevance
“…42 classes were selected for the generation of an initial model using e2initialmodel.py. In the following steps, reference-free 2D classification was performed in ROME (Wu et al, 2016), whereas unsupervised 3D classification was performed in RELION 1.3 (Scheres, 2012b). After the first round of reference-free 2D classification using all 250,251 particles binned to a pixel size of 4.00 Å, bad particles and non-RP class averages were rejected as a whole class upon inspection of class average quality.…”
Section: Star*methodsmentioning
confidence: 99%
“…42 classes were selected for the generation of an initial model using e2initialmodel.py. In the following steps, reference-free 2D classification was performed in ROME (Wu et al, 2016), whereas unsupervised 3D classification was performed in RELION 1.3 (Scheres, 2012b). After the first round of reference-free 2D classification using all 250,251 particles binned to a pixel size of 4.00 Å, bad particles and non-RP class averages were rejected as a whole class upon inspection of class average quality.…”
Section: Star*methodsmentioning
confidence: 99%
“…After auto-picked and verified using RELION 2.1 (41) and EMAN2 software (42), 835,709 particles of RyR1 were extracted from 9,528 good micrographs for the following analysis. All reference-free 2D and 3D classifications were carried out in RELION 2.1/3.0 (41) and ROME 1.1 (43), which combined the regularized maximum-likelihood based image alignment and manifold learning-based classification. 3D refinement that refined the Euler angles and x/y-shifts of each particle to further improve the resolution of density maps was completed in RELION.…”
Section: Methodsmentioning
confidence: 99%
“…After several rounds of iterative 2D and 3D classifications, bad particles and non-particle In order to improve the local resolution of density maps, the CTF parameters of each individual particle were refined locally with program Gctf (40). Based on the x/y-shift and orientation parameters of each particle from the high-resolution 3D refinement, we reconstructed two halfmaps of each state using raw single-particle images at super-resolution mode with a pixel size of 0.685 Å by ROME software (43). The global resolutions of the finial reconstructions of states 1, 2 and 3 were 2.6, 3.3 and 6.3 Å respectively, measured by the gold-standard Fourier shell correlation (FSC) at 0.143-cufoff on two independently refined half-maps.…”
Section: Methodsmentioning
confidence: 99%
“…[45] Single-particlec ryo-EM has been recentlye mployed to determine both protein structures and dynamics in their native, or even intermediate functional states, down to nearatomic resolution, [46] thanks to the application of direct electron detectors, as well as that of machine-learning-based data processing technology. [47] The direct electron detector has significantly enhanced the signal-to-noise ratio of recordedc ryoelectron micrographs.T he entire structures of DNA origami assembliesc an be preferably analyzed in 3D through single-par-ticle cryo-EM analysis. In 2012, Bai et al reported the first DNA origami structure resolved by using cryo-EM, with an overall resolution of 11.5 .…”
Section: Application Of Dna Origami In Cryo-em Analysis Of Protein Stmentioning
confidence: 99%